2017
DOI: 10.1186/s40795-017-0189-4
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between health and agriculture sectors in Ethiopia: a formative research study exploring barriers, facilitators and opportunities for local level coordination to deliver nutritional programmes and services

Abstract: Background: In Ethiopia, poor infant and young child feeding practices and low household dietary diversity remain widespread. The Government has adopted the National Nutrition Programme that emphasizes the need for multisectoral collaboration to effectively deliver nutrition-sensitive and nutrition-specific interventions. The Sustainable Undernutrition Reduction in Ethiopia (SURE) programme is one such Government-led initiative that will be implemented jointly by the health and agriculture sectors across 150 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This is similar to other studies 25,26 that review the practical implication of linkages between agriculture and health sector which reported that funding and budget controls as the core reason why there was little interaction between the two sectors. A similar study 27 in Ethiopia also identi ed lack of resources within individual sectors as barriers to effective coordination between health and agriculture and these studies recommended development of joint work plan with budget allocated for all activities to be implemented by both sectors for effective integration of intervention.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is similar to other studies 25,26 that review the practical implication of linkages between agriculture and health sector which reported that funding and budget controls as the core reason why there was little interaction between the two sectors. A similar study 27 in Ethiopia also identi ed lack of resources within individual sectors as barriers to effective coordination between health and agriculture and these studies recommended development of joint work plan with budget allocated for all activities to be implemented by both sectors for effective integration of intervention.…”
Section: Discussionmentioning
confidence: 96%
“…Another study in 27 Ethiopia on linkages between health and agriculture sectors also identi ed presence of competing priorities within individual sectors as barriers to effective coordination between the two sectors and the studies recommended inclusion of the integrated activities in the workplan or deliverables of the staffs in the health and agriculture sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition has been identified as a target public health problem among children and women in Ethiopia [ 13 , 14 ]. Improving collaboration across the nutrition and agriculture sectors in planning, monitoring, and evaluation to link nutrition and agriculture is crucial for the country to address the continued high prevalence of malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia has implemented multiple nutrition-specific and nutrition-sensitive programs such as the Ethiopian national nutrition program, and the Seqota declaration program, that have required the development of structures and processes that facilitate multisectoral coordination [15]. But, collaborations between the health and agriculture sectors are suboptimal at community levels [16]. The multi-sectoral nutrition programs and interventions lack strong coordination that brings on board all the relevant stakeholders.…”
Section: Introductionmentioning
confidence: 99%